The legal framework to protect electronic network users (comparative study) (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to identify the most prominent risks of using the Internet at the level of individuals and organizations, and to identify the legal and technological foundations necessary to protect Internet users. The study relied on a descriptive approach by reviewing and analysing studies and reports related to the subject of the study. The study is divided into two sections The study dealt with the dangers of using the Internet on individuals and institutions, and the legal and technological foundations for providing protection to individuals and institutions when using the Internet networks. The study concluded a set of conclusions, the most important of which are: The risks of using the Internet vary at the level of individuals and organizations. Facing the risks of using the Internet requires an integrated set of criminals, civil and other laws, as well as cooperation from institutions related to Internet services. In conclusion, the study recommended the need for international coordination to form an international organization concerned with issuing transnational laws to confront electronic crimes and risks.